Cross-border bank contagion in Europe - Reint E. Gropp; Marco Lo Duca; Jukka Vesala (European Central Bank (ECB), 2006)
This paper analyses cross-border contagion in a sample of European banks from January 1994 to January 2003. We use a multinomial logit model to estimate the number of banks in a given country that experience a large shock on the same day (“coexceedances”) as a function of variables measuring common shocks and lagged coexceedances in other countries. Large shocks are measured by the bottom 95th percentile of the distribution of the daily percentage change in the distance to default of the bank. We find evidence in favour of significant cross-border contagion. We also find some evidence that since the introduction of the euro cross-border contagion may have increased. The results seem to be very robust to changes in the specification.
Keywords: G21; F36; G15; 330; banking; Contagion; Distance to default; Multinomial logit model; Finanzmarkt; Kreditgeschäft; Kapitalmobilität; Eurozone; EU-Staaten